The great big book of families - Hoffman, Mary, 1945-; Asquith, Ros (New York : Dial Books for Young Readers, 2011)
An illustrated overview of families, examining various aspects of families from houses to holidays to schools and pets, and discussing feelings and family trees.
Booklist
Kirkus Starred
Publisher's Weekly
Booklist, March 2011
Kirkus Starred, March 2011
Publisher's Weekly, February 2011
Keywords: Families -- Juvenile literature; Families; Family; Picture books for children